Transcriptomics analysis of ethanol treatment of male Aedes aegypti reveals a small set of putative radioprotective genes - Pinch, Matthew; Bendzus-Mendoza, Harley; Hansen, Immo A. (Frontiers in Physiology, 2023)
Sterile Insect Technique (SIT) is based on releasing sterilized male insects into wild insect populations to compete for mating with wild females. Wild females mated with sterile males will produce inviable eggs, leading to a decline in population of that insect species. Sterilization with ionizing radiation (x-rays) is a commonly used mechanism for sterilization of males. Since irradiation can cause damage to both, somatic and germ cells, and can severely reduce the competitiveness of sterilized males relative to wild males, means to minimize the detrimental effects of radiation are required to produce sterile, competitive males for release. In an earlier study, we identified ethanol as a functional radioprotector in mosquitoes. Here, we used Illumina RNA-seq to profile changes in gene expression of male Aedes aegypti mosquitoes fed on 5% ethanol for 48 hours prior to receiving a sterilizing x-ray dose, compared to males fed on water prior to sterilization. RNA-seq revealed a robust activation of DNA repair genes in both ethanol-fed and water-fed males, but surprisingly few differences in gene expression between ethanol-fed and water-fed males. While differences in gene expression due to ethanol exposure were minimal, we identified a small group of genes that may prime ethanol-fed mosquitoes for improved survivability in response to sterilizing radiation.